India, Russia and Iran: a New Study on “North — South” International Transport Corridor - V. I. Belov (Yurtaev); . Binish (Informaciâ i Innovacii, 2022)
The International North-South Transport Corridor (INSTC) has made impressive progress in making boat, street, and rail courses that transport cargo between India, Iran and Russia and countries of the European Union and Central Asia. It connects India Ocean, Iran, the Persian Gulf nations, through the nations of the Caucasus and Central Asia with Russia and mainland Europe. This task was a reaction to Eurasian coordination, “Extraordinary Eurasian Partnership” (Russia, 2011) including “One Belt, One Road” (China, 2013) and The Silk Road. By rethinking the Integration and Economic Potential of the INSTC and its importance for the partaking nations, it is feasible to utilize the rationale of the aggregate game plan of the Eurasian space in light of a legitimate concern for all member states. However, the first trail train via INSTC, departing from Helsinki on June 21, 2021, arrived at its destination at twice the speed of the existing Suez Canal route, proving the timeliness and competitiveness but missing rout in Iran Rasht-Astara railway line still remain the challenging problem for the Iranian government as well as for India and Russia.